Tourmaline chemistry in the Miocene and Paleozoic granites, Central Nepal Himalaya (Journal of Nepal Geological Society, 2004)
Tourmalines are found in almost all the formations, from the Lesser Himalaya to the Tibetan-Tethys Himalaya. They are equally found in the Miocene and Paleozoic granites in Central Nepal. Aplite-pegmatite dykes and Miocene granite from the Higher Himalaya, Tibetan-Tethys Himalaya also contain the tourmaline.The chemical composition of tourmalines from the Miocene granite, Paleozoic granite, and aplite pegmatites is presented in schorlite (Fe)-dravite (Mg)-elbaite (Al) diagram. The tourmalines from the granites are schorlitic (rich in Fe) in composition. No compositional variation between rim and core of the tourmaline in augen gneiss of the Formation III of the Higher Himalaya could correspond to the recrystallization of the tourmaline during the Himalayan metamorphism. The tourmalines from Manaslu and Chhokang granites can be evolved from Mg rich composition in higher temperature towards the Fe rich in lower temperature during the crystallization reflected by the XFe variation. Similarly, the composition of tourmalines is found to evolve from dravite (Mg rich) in the aplite-pegmatite dykes of the Higher Himalaya to schorlite (Fe rich) and elbaite (Al) in the aplite-pegmatite dykes of the Annapurna Formation of the Tibetan-Tethys Himalaya and Manaslu granite.The aplite-pegmatite dykes intruded into the pelitic rocks contain Mg rich tourmalines while Fe rich tourmalines are found in calcareous host rocks. So, the composition of the tourmalines of aplite-pegmatites can not be controlled by the composition of host rocks, but it is indirectly controlled by the composition of fluid phase of magma.